COMPARING THE WMA AND SES METHODS FOR FORECASTING STOCK PRODUCT OF MS GLOW PUTRI - Nurhamidah, Nurhamidah; Sembiring, Muhammad Ardiansyah; Lubis, Iin Almeina (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Ms Glow Putri Shop is a business that operates in the beauty sector, selling beauty products, namely skincare and bodycare, which are useful for maintaining healthy body and facial skin. However, Ms Glow Putri currently often experiences problems, namely tight competition and inventory management that is less effective in terms of sales numbers. Every month reaching ±1300 products, Ms Glow Putri also often experiences shortages and build-ups in skincare and bodycare stocks. This can reduce customer confidence so that Ms Giow Putri often experiences losses in the form of finance and other things, so this method is needed to predict some skincare and other stock supplies. bodycare provided in the following month. This method uses the Weighted Moving Average and Single Exponentiation Smoothing methods to predict supplies of skincare and bodycare stocks. The results of research on Ms GIow daughter using the Weight Moving Average Method with a weight of 5 with a MAPE of 1.08% and the SingIe Exponentiation Smooting Method with an Alpha of 0.1, namely 0.84%, then the comparison between the two methods can be stated that the SES method is the best method good, because it has the lowest error.      Keywords: forecasting; ms glow putri; ses and wma Abstrak: Toko Ms Glow Putri adalah usaha yang bergerak di bidang kecantikan, menjual produk kecantikan yaitu skincare dan bodycare berguna untuk menjaga agar kesehatan kulit tubuh dan wajah tetap terjaga. Namun Ms Glow Putri saat ini sering kali mengalami permasalahan yaitu persaingan yang ketat dan manajemen persediaan yang kurang efektif dengan jumlah penjualanan. Setiap bulan mencapai ±1300 produk maka Ms Glow Putri juga sering mengalami kekurangan dan penumpukan pada stok skincare dan bodycare ini dapat mengurangi kepercayaan pelanggan sehingga Ms Glow Putri sering mengalami kerugian berupa finance dan lainnya maka perlu metode ini untuk memprediksi beberapa persediaan stok skincare dan bodycare yang disediakan pada priode di buIan berikutnya. Metode ini menggunakan metode Weighted Moving Averege dan Single Exponential Smoothing untuk memprediksi persediaan pada stok skincare maupun bodycare. HasiI penelitian pada Ms GIow Putri dengan mengggunakan Metode Weight Moving Averege dengan bobot 5 dengan MAPE 1,08% dan Metode Single Exponential Smooting dengan Alpha 0,1 yaitu 0,84% maka perbandingan antara dua metode tersebut dapat dinyatakan bahwa metode SES adaIah metode paling baik karena memiliki error terendah. Kata kunci: ms glow putri; peramalan; ses dan wma